Comprehensive characterization of novel Robusta (AAA) banana bracts fibers reinforced polylactic acid based biocomposites for lightweight applications. Issue 11 (2nd September 2022) - Ramasamy, Siva; Karuppuchamy, Amutha; Jayaraj, Jeya Jeevahan; Suyambulingam, Indran; Siengchin, Suchart; Fischer, Steffen
Abstract: Biocomposites have attracted researchers recently due to their biodegradability and environment‐friendly nature. The application of new fibers is increasing to reduce the fiber cost, and easy processing, and to meet the application‐specific properties in composite manufacturing. Banana is one of the most investigated plants for extracting fibers. Literature showed that the banana fibers were extracted from various parts of the plant. However, the potential of banana bracts is not discovered yet for composite manufacturing. In this work, the Robusta (AAA) variety banana bracts fibers (BBF) were prepared and used to make BBF reinforced polylactic acid (PLA) matrix biocomposites. Virgin PLA and BBF/PLA composites were prepared by two roll mills followed by compression molding. The characterization was carried out through X‐ray diffraction (XRD), Fourier transform infrared (FTIR), thermogravimetric analysis (TGA), and scanning electron microscopy (SEM), and the tensile, flexural, and impact properties were evaluated for Virgin PLA, BBF, and BBF/PLA composites. The FTIR results supported the incorporation of banana bracts in the composites by increasing the cellulosic and noncellulosic components. The SEM images supported the bonding of BBF in the PLA matrix. The BBF/PLA composite possessed the tensile strength of 40.15 ± 4.32 MPa, flexural strength (FS) of 87.13 ± 5.60 MPa, impact strength of 7.41 ± 0.56 kJ/m 2, and a crystallinity index of 48.22%, which were significantly better than the virgin PLA. It was concluded that the BBF can be effectively used for making biocomposite with good mechanical strength.